Designing a Student Violation Point System Based on Telegram Using PHP Programming Language - Khoirullah, Khoirullah; Supriadi, Supriadi; Zakir, Supratman; Efriyanti, Liza (Knowbase : International Journal of Knowledge in Database, 2023)
This research is motivated by an issue concerning student violations at Tugumulyo State Vocational High School which are still frequently occurring, and the recording of these student violations is manually documented in a student violation logbook, causing difficulties for the guidance and counseling teachers in managing them. Furthermore, parents face challenges in monitoring their children's discipline at school due to the insufficient delivery of information regarding student violation points. Hence, there is a need for a system capable of managing student violation data and providing information to parents regarding their children's discipline in school. This research applies the Research and Development (R&D) model. The R&D model in this research employs the ADDIE model with five stages: Analyze, Design, Develop, Implement, and Evaluate. This product has been tested for validity, practicality, and effectiveness. The results of the product's validity test obtained a score of 0.85, categorized as valid. The practicality test resulted in a score of 0.97, categorized as a very high level of practicality, while the effectiveness test yielded a score of 0.91, categorized as a high level of effectiveness. These research findings demonstrate that the integrated student violation point system through Telegram at Tugumulyo State Vocational High School has been proven to be valid, practical, and effective.